2011
DOI: 10.1016/j.jacc.2011.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Src Tyrosine Kinase Prevents Angiotensin II–Mediated Connexin-43 Remodeling and Sudden Cardiac Death

Abstract: Objectives We sought to test whether c-Src tyrosine kinase mediates connexin 43 (Cx43) reduction and sudden cardiac death in a transgenic mouse model of cardiac-restricted overexpression of angiotensin-converting enzyme (ACE8/8). Background Renin-angiotensin system (RAS) activation is associated with an increased risk of arrhythmia and sudden cardiac death; however, that mechanism is not well understood. The upregulation of c-Src by angiotensin II may result in the reduction of Cx43, which impairs gap juncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 29 publications
3
95
0
Order By: Relevance
“…It has been shown that cardiomyopathy is associated with oxidative stress, which is an imbalance between the production and neutralization of reactive oxygen species [8]. In addition, several experimental studies suggest that oxidant stress can lead to focal activity and reentry, and is a cause of VT [9, 10]. Serum UA is a metabolic product in the terminal stage of purine metabolism produced via the action of xanthine oxidase, an enzyme that is implicated in oxidative processes [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cardiomyopathy is associated with oxidative stress, which is an imbalance between the production and neutralization of reactive oxygen species [8]. In addition, several experimental studies suggest that oxidant stress can lead to focal activity and reentry, and is a cause of VT [9, 10]. Serum UA is a metabolic product in the terminal stage of purine metabolism produced via the action of xanthine oxidase, an enzyme that is implicated in oxidative processes [11].…”
Section: Discussionmentioning
confidence: 99%
“…A modified protocol from Sovari et al17 was used to evaluate GJ function in WT and GCα1‐KO mice hearts. Hearts were harvested and washed in PBS, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the GCα1‐KO mouse model, we used an angiotensin II (AngII)–induced cardiac hypertrophy mouse model because AngII‐treated animals have decreased NO‐stimulated GC1 activity in the cardiovascular system 15. In our specific model, we observed cardiac hypertrophy, but the cardiac remodeling associated with arrhythmic sudden death and heart failure has not yet taken place, unlike other renin‐angiotensin mouse models 16, 17…”
mentioning
confidence: 99%
“…Cx43 upregulation occurs primarily at the intercalated disks and correlates with gap junction functional improvement, and associated with a reduced risk of ventricular tachycardia inducibility and SCD. The activation of renin-angiotensin system is associated with c-Src upregulation, Cx43 loss, reduced myocyte coupling and arrhythmic sudden death (43).…”
Section: Conservative Treatmentmentioning
confidence: 99%